The Transformation of the Iranian Charshanbe Suri Festival in the Yezidi Tradition - Tereza Amryan (Banber Arevelagitut'yan Instituti)
The aim of this article is to clarify the transformation of the Iranian Charshanbe Suri festival in the Yezidi religious system. Charshanbe Suri is celebrated on the eve of the last Wednesday before the Iranian New year - Nōwrūz. It is considered to be the point of transition between the old and new years and is associated with cleansing and purifying. Yezidis celebrate Charshama Sor on the first Wednesday after April 13 (according to the Gregorian Calendar). Unlike Charshanbe Suri, Charshama Sor is not considered a transition between the old and new years. Charshama Sor symbolizes the awakening of nature, the arrival of Spring, the New Year, as well as cosmogony, the creation and renewal of the world, and the “birth” of one of the Yezidi saints, Tausi Malak. There is no doubt that the Yezidi Charshama Sor is a version of the Iranian Charshanbe Suri. This study of Charshama Sor reveals that the Yezidi tradition has preserved Charshanbe Suri and its main symbols but has also endowed it with new, Yezidi interpretations.